Financial Innovation, Bank Liquidity and Entrepreneurship Support: An Analytical Evidence from Commercial Banks in Bamenda, Cameroon - Maurice Ayuketang Nso; Njekang Dieudonne Nkwati; Ngoh Christopher Sam; Humphred Watard (European Scientific Journal, ESJ, 2025)
Commercial bank liquidity remains a critical issue globally, especially in an emerging city like Bamenda, Cameroon, where fluctuating liquidity levels pose challenges to financial stability and operational efficiency for banks. The main objective of this study is to examine the effect of financial innovation and entrepreneurship support on the liquidity position of commercial banks in Bamenda. Employing a cross-sectional survey design, primary data were collected through structured questionnaires from 39 bank officials. The data were analysed using a multinomial cumulative probit model to capture the ordinal nature of the variables under examination. The findings indicate that financial innovation has a statistically significant effect on bank liquidity, whereas entrepreneurship support shows a non-significant negative effect. The model’s goodness-of-fit measures suggest a robust representation of the data, and the results reveal that financial innovation has a more prominent effect on liquidity position than entrepreneurship support within the context of the study. Based on these findings, it is recommended that banks and policymakers enhance the development and adoption of innovative financial solutions to optimize resource allocation and stabilize liquidity levels. Additionally, fostering entrepreneurship through targeted financial products could further improve liquidity resilience. Strengthening capacity-building initiatives on financial innovations and entrepreneurship financing is crucial to ensuring sustainable liquidity management and economic growth in Bamenda’s banking sector.